Narratives of Ageing and Memory in Contemporary Global North Cinema: Analyzing the Impact of COVID-19 - Atenas, Rodriguez Julieta (Magyar Gerontológia, 2024)
Media representation, such as shows and films, are commonly the primary source through which younger people encounter a variety of depictions of old age and medical conditions. These portrayals significantly shape public perceptions. Taking this into consideration this research investigates contemporary portrayals of ageing and memory, with a particular focus on dementia, in Global North cinema. It examines how recent Western films reflect a change of the societal perceptions of ageing and memory in the aftermath of the COVID-19 pandemic.